Is There a Union Wage Premium in Germany and Which Workers Benefit Most? - Marina Bonaccolto-Töpfer; Claus Schnabel (Institute of Labor Economics (IZA), 2023)
Using representative data from the German Socio-Economic Panel (SOEP), this paper finds a statistically significant union wage premium in Germany of almost three percent which is not simply a collective bargaining premium. Given that the union membership fee is typically about one percent of workers' gross wages, this finding suggests that it pays off to be a union member. Our results show that the wage premium differs substantially between various occupations and educational groups, but not between men and women. We do not find that union wage premia are higher for those occupations and workers which constitute the core of union membership. Rather, unions seem to care about disadvantaged workers and pursue a wider social agenda.
Keywords: J31; J53; 330; union membership; collective bargaining; union wage premium; Germany